Diagnostic challenges in assessing treatment responds of primary bone lymphoma: A case report - Angelina, Arlene; Kusumahstuti, Kharisma; Darmawan, Budi; Hidayat, Basuki (Deka in Medicine, 2025)
BACKGROUND: Primary Bone Lymphoma (PBL) is quite difficult to assess treatment responses because of limited access to 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT). Therefore, this study intends to highlight one case regarding alternative imaging modalities, such as technetium-99m methylene diphosphonate (99mTc-MDP) and technetium-99m methoxyisobutyl isonitrile (99mTc-MIBI), for activity assessment in tumors as well as their involvement in the marrow. CASE: A 17-year-old male with persistent pain and swelling in the left knee over one month underwent a bone biopsy that confirmed the diagnosis of Diffuse Large B-Cell Lymphoma (DLBCL) in the tibia. The patient was subjected to chemotherapy using cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP), followed by radiotherapy. PET/CT was unavailable; therefore, metabolic tumor evaluation was performed through 99mTc-MDP and 99mTc-MIBI scintigraphy for tumor activity and bone marrow involvement assessment. Bone scintigraphy with 99mTc-MDP showed increased tracer uptake in the proximal left tibia and distal left femur, indicating ongoing tumor activity. These findings were reinforced by the further assessment with 99mTc-MIBI, which confirmed high metabolic activity in these areas. Subsequently, a bone marrow biopsy evidenced infiltrative lymphoblasts constituting 24.8 percent infiltrating the involved marrow space, thus confirming the bone marrow being infiltrated. Hence, this patient received additional rituximab treatment to enhance treatment outcome. CONCLUSION: This case portrays the difficulties one faces while evaluating the treatment response in Primary Bone Lymphoma (PBL), as well as the role of 99mTc-MDP and 99mTc-MIBI scintigraphy as alternative metabolic imaging modalities in the absence of PET/CT.